2008
DOI: 10.1016/j.atherosclerosis.2007.01.036
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a locus modulating serum C-reactive protein levels on chromosome 5p15

Abstract: Objective: Individual propensity to chronic, low-grade inflammation -a determinant of atherosclerosis -is in part under the control of genetic factors. To identify genes involved in this modulation, we performed a 10 cM genome screen for linkage with plasma C-reactive protein in 38 extended families including 317 non-diabetic and 177 type 2 diabetic family members (2,547 relative pairs). Methods and results:In a variance component analysis, heritability of CRP values was significant (h 2 =0.39, p<0.0001). This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 34 publications
1
10
0
Order By: Relevance
“…This provides evidence for common, yet unidentiWed genetic factors inXuencing jointly BMI and CRP beyond the CRP gene itself. While we could not detect a signiWcant environmental correlation between CRP levels and BMI, a recent genome scan for CRP by Keenan et al (2007) demonstrated that the relationship between CRP and BMI was mostly environmental within their study population. This diVerence is likely due to the diVerent ascertainment criteria among the studies.…”
Section: Discussionmentioning
confidence: 58%
“…This provides evidence for common, yet unidentiWed genetic factors inXuencing jointly BMI and CRP beyond the CRP gene itself. While we could not detect a signiWcant environmental correlation between CRP levels and BMI, a recent genome scan for CRP by Keenan et al (2007) demonstrated that the relationship between CRP and BMI was mostly environmental within their study population. This diVerence is likely due to the diVerent ascertainment criteria among the studies.…”
Section: Discussionmentioning
confidence: 58%
“…[11][12][13] In the present study of sibships ascertained based on hypertension, we found plasma levels of CRP and fibrinogen to be moderately heritable, consistent with earlier studies. [11][12][13]33,34 The heritability of plasma fibrinogen levels was greater in African Americans (h 2 = 0.44) than in non-Hispanic whites (h 2 = 0.28), suggesting a stronger additive genetic contribution to this trait in African Americans. Significant phenotypic and genetic correlations between plasma CRP and fibrinogen levels were present in both African Americans and non-Hispanic whites, indicating that shared genes and environment influence interindividual variation in CRP and fibrinogen levels.…”
Section: Discussionmentioning
confidence: 99%
“…In a third study, results from two independent Caucasian populations revealed a QTL for CRP levels on chromosome 10 (at 141 cM) with LOD scores of 3.2 and 2.7 (Broeckel et al 2007) with other putative QTLs on chromosomes 5 (at 150 cM), 2 (10 cM) and 16 (at 30 cM). Finally, evidence of linkage on chromosome 5p15 (LOD = 3.41) was found in a fourth study (Keenan et al 2008).…”
Section: Introductionmentioning
confidence: 98%
“…Genetic factors have been reported to explain part of these variations. Depending on the ethnic group and the statistical adjustment for co-variables, the additive genetic heritability was estimated to be between 39 and 70% for adiponectin levels (Chuang et al 2004;Comuzzie et al 2001;Lindsay et al 2003;Pollin et al 2005), 17-69% for IL-6 (de Maat et al 2004;Dupuis et al 2005;Grunnet et al 2006;Pantsulaia et al 2002), 26-68% for TNF-a (de Maat et al 2004;Pantsulaia et al 2002) and 30-40% for CRP (de Maat et al 2004;Dupuis et al 2005;Keenan et al 2008;Lakka et al 2006;Pankow et al 2001).…”
Section: Introductionmentioning
confidence: 99%